A Lifestyle Risk Reduction Model for Preventing High-Risk Substance Use Across the Lifespan - Dykstra, Rita E.; Beadnell, Blair; Rosengren, David B.; Schumacher, Julie A.; Daugherty, Raymond (Prevention science, 2023)
While effective models of alcohol and drug prevention exist, they often focus solely on youth or young adults. This article describes the Lifestyle Risk Reduction Model (LRRM), an approach applicable across the lifespan. The intent behind the LRRM is to guide the development of prevention and treatment programs provided to individuals and small groups. The LRRM authors’ goals are to help individuals reduce risk for impairment, addiction, and substance use’s negative consequences. The LRRM identifies six key principles that conceptualize the development of substance-related problems by drawing parallels with health conditions, such as heart disease and diabetes, which often result from combined effects of biological risk and behavioral choices. The model also proposes five conditions that describe important steps for individuals as they progress toward greater perception of risk and lower risk behavior. One LRRM-based indicated prevention program (Prime For Life) shows positive results in cognitive outcomes and in impaired driving recidivism for people across the lifespan. The model emphasizes common elements across the lifespan, responds to contexts and challenges that change across the life course, complements other models, and is usable for universal, selective, and indicated prevention programs.